The Media Of Bugis Literacy: A Coda To Pelras - Macknight, Campbell (Penerbit Universiti Sains Malaysia (USM Press), 2016)
The existence of literacy implies a range of practical questions about writing. While attention has been given to the form of Bugis writing, there are also issues around the mechanics of writing, that is, the ways in which marks have been made on various surfaces. Bugis literacy, which began with palm leaf manuscripts, has been overwhelmingly in the form of paper manuscripts, though examples of printing, inscriptions on silver and on earthenware are also discussed and illustrated. The relationship between medium and the function of writing is explored in particular cases.